Exploring Students’ Perceptions in English Blended (Online and Offline) Learning to Foster Listening Skills - Nazwa Zein; Alifia Rahmani Gunawan; Fitria Nurul Hasanah; Haryanti Haryanti (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This research aimed to investigate students’ perceptions, difficulties and learning experiences in a blended listening class situation. In the present qualitative study, thirty (30) English Language Teaching (ELT) undergraduate students were selected using a purposeful sampling to be the research participants. Open-ended questionnaires were distributed for data collection. Then, the data collected were analyzed through reflexive thematic analysis, so as to interpret the findings and further understand students’ experiences. Results indicated that students appreciated the independence that was afforded online, such as being able to pause audio and access transcripts, but they enjoyed face-to-face sessions for the feedback they could obtain and the questions they could ask. Though faced with issues like technical problems and struggling to focus on learning, it is concluded that a blended approach can be both effective and efficient if the online and offline components are well-integrated and supported by an appropriate system, which makes it also highly applicable in EFL.